TANGGUNG JAWAB DEVELOPER TERHADAP KONSUMEN AKIBAT WANPRESTASI DALAM PENYERAHAN UNIT APARTEMEN PLUIT SEA VIEW BERDASARKAN PERJANJIAN PENGIKATAN JUAL BELI - Natalia Salim; Endang Pandamdari (Jurnal Hukum Adigama, 2019)
The procurement of an apartment is strengthened by Sales and Purchase Agreement (PPJB) between the buyer and the developer, but the practice in the field are often found that developers does not handover the physical terms in accordance with the agreed time (default/breach of contract), and resulting in losses for the buyer. This study aims to determine the responsibility of the developer to the buyer due to default/breach pf contract matter and legal protection for the buyer in terms of buying Pluit Sea View apartments based on Sale and Purchase agreement. Research data were analyzed using descriptive-qualitative analysis methods which were tested with legal norms. The result of analysis shows that: 1. PT.  Binakarya Bangun Propertindo (as developer) does not fulfill their responsibilities as in agreement of the PPJB regarding the rights of consumers. 2. Weak of Consumer Protection Sarusun Belonging to Pluit View Sea , as consumer do not have bargaining positions.